2021
DOI: 10.1007/s40843-020-1611-9
|View full text |Cite
|
Sign up to set email alerts
|

A shape memory porous sponge with tunability in both surface wettability and pore size for smart molecule release

Abstract: Recently, smart superwetting porous materials have aroused much attention, and it is well known that tunable surface wettability and pore structure/size are extremely important for their functions. However, only one factor can be regulated on existing materials, which significantly restricts their controllability, functions, and applications. A new material was prepared by electrodepositing a layer of polypyrrole on a shape memory sponge, on which switchable superhydrophobicity/superhydrophilicity and adjustab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Researchers in the past used γ c as an extremely important empirical constant reflecting the wettability of solid surfaces with low surface energy. 45 Only the liquid with surface tension equal to or less than the surface γ c can spread on the solid surface, which means that the smaller the γ c value, the harder the surface is to wet. 46,47 In this experiment, PFDT was applied as a modifier to silver nanoparticles, which reduced the surface free energy of Ag and constructed nanostructures on the surface of the carbon paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in the past used γ c as an extremely important empirical constant reflecting the wettability of solid surfaces with low surface energy. 45 Only the liquid with surface tension equal to or less than the surface γ c can spread on the solid surface, which means that the smaller the γ c value, the harder the surface is to wet. 46,47 In this experiment, PFDT was applied as a modifier to silver nanoparticles, which reduced the surface free energy of Ag and constructed nanostructures on the surface of the carbon paper.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the terminal functional groups of the organic matter adsorbed on the surface will give new functions to the silver nanoparticles. Researchers in the past used γ c as an extremely important empirical constant reflecting the wettability of solid surfaces with low surface energy . Only the liquid with surface tension equal to or less than the surface γ c can spread on the solid surface, which means that the smaller the γ c value, the harder the surface is to wet. , …”
Section: Resultsmentioning
confidence: 99%
“…Reprogrammed micro/nanostructures that can reversibly deform into multiple configurations as demanded have aroused enormous research interests for its broad application prospects in controllable friction, , tunable wettability, optical engineering, etc. , Up to date, various responsive materials that respond to different stimuli (e.g., light, heat, electricity, and magnets. , ) including elastic polydimethylsiloxane (PDMS) substrate, magnetic substance, , shape memory polymers (SMPs), etc., have been adopted for realizing the controllable micro/nanostructure deformation. Among those, the SMPs possess particular advantages.…”
Section: Introductionmentioning
confidence: 99%
“…[46,47] Based on the excellent shape memory effect of these materials, more convenient control of surface wettings and lots of new functions have been reported. [48][49][50][51][52][53][54][55][56][57] For example, through reversibly controlling microscale pillar shape between upright and collapsed states, Yang et al, realized the wetting transition and demonstrated droplet shedding on the superhydrophobic shape memory surface; [58] by decorating the shape memory arrays the pH-responsive capsules, Wu et al, reported the self-healing function on the superhydrophobic SMP surface; [59] based on similar shape memory effect, we also achieved several important results, such as precise wetting control, [48,51] controllable droplet storage, [60] capture/ release, [61] programmable droplet motion, [62,63] directional/ anti-directional droplet sliding, [64] and so on. [65][66][67] Nevertheless, almost all these works are concentrated on superhydrophobic surface, related wetting control on slippery surfaces are still extremely rare and only reported in recently.…”
Section: Introductionmentioning
confidence: 99%